1999
DOI: 10.1074/jbc.274.40.28542
|View full text |Cite
|
Sign up to set email alerts
|

Novel Rabphilin-3-like Protein Associates with Insulin-containing Granules in Pancreatic Beta Cells

Abstract: A novel rabphilin-3-like gene, granuphilin, has been identified in pancreatic beta cells by comparing genes expressed in pancreatic alpha and beta cell lines using mRNA differential display. The domain structure of the protein products of the granuphilin gene contains an amino-terminal zinc-finger motif and carboxyl-terminal C 2 -domains, similar to that of the rabphilin-3 gene. There are two isoforms: the larger isoform, granuphilin-a, has two C 2 -domains, whereas the smaller one, granuphilin-b, contains onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
138
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 35 publications
8
138
0
1
Order By: Relevance
“…Using the specific antibodies against mouse Noc2, the present immunohistochemical study is the first to identify the cell types expressing All endocrine cell types in the adenohypophysis, pancreatic islets, and adrenal gland exhibited Noc2 immunoreactivity. Thus, the cellular distribution of Noc2 is broader than in the other two endocrine-type Rab effector proteins: granuphilin, which is detected in pancreatic β-cells and the pituitary gland (Wang et al 1999;Yi et al 2002), and Rim2, which is expressed in insulin cell lines, the pituitary gland, and PC12 cells, but not in the adrenal gland (Ozaki et al 2000). The association of Noc2 with secretory granules has been demonstrated in insulin-secreting β-cell lines (Cheviet et al 2004a) and PC12 cells (Fukuda et al 2004) (Garrett 1998).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using the specific antibodies against mouse Noc2, the present immunohistochemical study is the first to identify the cell types expressing All endocrine cell types in the adenohypophysis, pancreatic islets, and adrenal gland exhibited Noc2 immunoreactivity. Thus, the cellular distribution of Noc2 is broader than in the other two endocrine-type Rab effector proteins: granuphilin, which is detected in pancreatic β-cells and the pituitary gland (Wang et al 1999;Yi et al 2002), and Rim2, which is expressed in insulin cell lines, the pituitary gland, and PC12 cells, but not in the adrenal gland (Ozaki et al 2000). The association of Noc2 with secretory granules has been demonstrated in insulin-secreting β-cell lines (Cheviet et al 2004a) and PC12 cells (Fukuda et al 2004) (Garrett 1998).…”
Section: Discussionmentioning
confidence: 97%
“…This non-critical phenotye in β-cells may be explained by the multi-regulation of insulin secretion by different sets of Rab/effector. Endocrine cells including pancreatic β cells possess some potential Rab effectors other than Noc2, such as granuphilin (Wang et al 1999;Yi et al 2002) and Rim2 (Ozaki et al 2000), which were identified first in β cells and are suggested to be present in other amine/peptide-secreting endocrine cells. The normal insulin release in response to glucose and the normal morphology of β-cells in Noc2-knockout mice suggests a compensation for the Noc2 deficiency by granuphilin and Rim2 although the expression levels of granuphilin and Rim2, as assessed by RT-PCR, were similar in the knockout mice (Matsumoto et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA fragments of N-terminal exophilin4 encoding 1-462 and 1-381 amino acids were similarly amplified and subcloned into the pcDNA3-HA and pGEX4T-1, respectively. The GST-fused cDNA constructs containing 315-673 (C2AB domain), 315-502 (C2A domain), and 487-673 (C2B domain) amino acids of granuphilin-a and that encoding the C2A domain of rat synaptotagmin I (139-267 amino acids) were described previously (Wang et al, 1999). A cDNA fragment encoding the C2B domain of rat synaptotagmin I (248-421 amino acids) containing glycine at 374 (Desai et al, 2000) was synthesized by reverse transcription-PCR, by using rat brain RNA as a template, and fused to GST.…”
Section: Dna Constructionmentioning
confidence: 99%
“…However, little is known about possible differences in the exocytic machinery between these two cell types. We previously reported a novel protein product, granuphilin, that is specifically expressed in ␤ cells but not in ␣ cells (Wang et al, 1999). Subsequent analyses indicate that granuphilin functions as an effector of Rab27a and mediates docking of insulin granules to the plasma membrane in ␤ cells (Torii et al, , 2004Gomi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Synaptotagmin-like proteins (Slp) and the related Slac2 proteins (Slps lacking C2 domains) are characterized by the presence of a unique amino terminal domain that confers the capacity to bind Rab27 (Kuroda et al, 2002a(Kuroda et al, , 2002b. One member of this protein family, Slp4/Granuphilin is localized on secretory granules of pancreatic ␤-cells and its overexpression causes a profound inhibition of insulin secretion (Wang et al, 1999;Coppola et al, 2002;. This effect is prevented by point mutations that impair binding of Rab27 , suggesting that Slp4/Granuphilin may mediate at least part of the functions of this GTPase.…”
Section: Introductionmentioning
confidence: 99%